Combination Effect of Cecendet (Physalisangulata L.) Extract and Methylprednisolone in Reducing Inflammation and Improving Renal Functions in Pristane-induced Lupus Rat Models - Sheba, Shiane Hanako; Setiani, Nur Asni; Sutjiatmo, Afifah B.; Vikasari, Suci Nar; Sukandar, Elin Yulinah (Majalah Kedokteran Bandung, 2019)
Cecendet (Physalis angulata L.) is a herbal plant commonly used for traditional remedies in Indonesia to prevent inflammation in rheumatic disease. Several studies have determined that cecendet has an immunosuppressant activity towards pristane-induced lupus animal model. A preliminary study has proven that its use is safe in animals based on acute and sub-chronic toxicity tests. In management of lupus, methylprednisolone is used for primary immunosuppressant agent. This study aimed to investigate the effect of cecendet ethanolic extract in combination with methylprednisolone on inflammation, urinalysis, and serum creatinine level of rats as pristane-induced lupus animal models. This study was conducted at the Pharmacology Laboratory of Pharmacy Faculty of Jenderal Ahmad Yani University in January 2016. Four groups of female rats were used i.e. normal group, control group, 62.5 mg/kg body weight (BW) cecendet ethanolic extract group, and group receiving 62.5 mg/kg bw cecendet ethanolic extract combined with 0.36 mg/kg body weight methylprednisolone for six weeks, followed by thirty days of 0.5 mL pristine-induced. Examinations on anti-inflammation effect, urinalysis, and serum creatinine level were performed in week 3 and 6 during the intervention. The results showed that the administration of cecendet ethanolic extract alone and in combination with methylprednisolone could inhibit inflammation and reduce proteinuria and serum creatinine level when compared to the control group.Key words: Anti-inflammation, cecendet, creatinine, methylprednisolone, Physalis angulata L. Pengaruh Pemberian Kombinasi Ekstrak Cecendet (Physalisangulata L.) dan Metilprednisolon terhadap Penurunan Radang dan Perbaikan Fungsi Ginjal Pada Model Tikus Lupus yang Diinduksi PristanaTanaman cecendet (Physalis angulata L.) sering digunakan sebagai obat tradisional di Indonesia, antara lain sebagai antiradang untuk mengobati reumatik. Penelitian terdahulu menunjukkan bahwa cecendet memiliki aktivitas imunosupresan pada hewan model lupus yang diinduksi pristana dan aman berdasar s ata uji toksisitas akut dan subkronis. Pada penanganan lupus, metilprednisolon digunakan sebagai obat utama imunosupresan. Penelitian ini bertujuan menguji khasiat ekstrak etanol herba cecendet dalam penggunaan tunggal dan kombinasi dengan metilprednisolon terhadap radang, urinalisis, dan kadar kreatinin serum pada tikus yang diinduksi pristana sebagai model hewan lupus. Penelitian dilaksanakan di Laboratorium Farmakologi Fakultas Farmasi Universitas Jenderal Ahmad Yani pada bulan Januari 2016. Tikus betina sebagai hewan uji dibagi menjadi 4 grup, yaitu: grup normal, grupkontrol, grup diberi sediaan ekstrak etanol herba cecendet 62,5 mg/kg BB tunggal, dan grup hewan uji diberi sediaan ekstrak etanol herba cecendet 62,5 mg/kg BB kombinasi dengan metilprednisolon 0,36 mg/kg BB selama enam minggu, setelah tiga puluh hari diinduksi 0,5mL pristana. Tiga dan enam minggu setelah pemberian sediaan uji, dilakukan uji efek antiradang, pemeriksaan urin, dan pengukuran kadar kreatinin serum. Hasil penelitian menunjukkan bahwa pemberian ekstrak etanol herba cecendet tunggal maupun sebagai komplemen dengan metilprednisolon selama enam minggu memperlihatkan pengaruh penghambatan pembentukan radang, menurunkan proteinuria dan menurunkan kadar kreatinin serum jika dibanding dengan kelompok kontrol.Kata kunci: Anti-radang, Cecendet, kreatinin, metilprednisolon, Physalis angulata L.